Event-based road safety assessment: A novel approach towards risk microsimulation in roundabouts. (1st December 2020) - Bulla-Cruz, Lenin Alexander; Laureshyn, Aliaksei; Lyons, Liliana
Graphical abstract: Highlights: Event-based microsimulation safety assessment is a promising tool under development. Safety distance factor of VISSIM conflict areas is a key parameter. It is possible to simulate exposure as well as event-based risk. Exposure explains the conflict frequency in a good way. Observed and simulated conflicts/encounters ratio shows the risky activity. Abstract: Conventional road accident risk is measured by the undesirable events/exposure ratio. Common exposure indicators are activity-based, so event-based exposure is needed to achieve event-based safety assessment. Furthermore, road safety simulation is a growing research field. The influence of some software parameters is still unknown. Besides, the use of simulation for exposure assessment is incipient. This paper aims to validate a preventive event-based risk indicator: traffic conflicts/encounters, extending to risk microsimulation by a novel procedure to identify encounters in VISSIM. We evaluated the safety of a roundabout by three independent methods: [i] Swedish Traffic Conflict Technique using T-Analyst tool, [ii] VISSIM/SSAM conflict analysis, and, [iii] exposure mapping using encounters. Findings show that, once calibrated the safety distance factor of VISSIM conflict areas at 0.5, we got a similar number of observed and simulated conflicts, similar severities and similar number of encounters, resulting in similar observed and simulated risk outcomes.